Level of Student Satisfaction on Quality of Private Higher Education Service - Irsutami Irsutami; Apri Apri (Pusat P2M Politeknik Negeri Batam, 2017)
The research examines the level of student satisfaction with quality of services of university. Quality of service is measured by the five dimensions namely Tangible, Reliability, responsiveness, Assurance and Empathy. The data used in this research is primary data therefore this research using a questioner. Distributed questioner to students as many as 80 active academic year 2014/2015. Successfully complete questionnaires and return as many as 80 questionnaires. Measuring the level of satisfaction by asking the perceptions and expectations of students against five dimensions of quality. In general, the results showed that the research feel quite satisfied with the service quality dimensions, but there are several indicators in the dimensions that should be of concern GBSB organizers to create better satisfaction.